MAHMUDHOJA BEHBUDIY: REPRESENTATIVE OF THE JADIDIST MOVEMENT AND HIS FOLLOWERS - Choriyeva Ma’mura (American Journals, 2025)
This article discusses the importance of the Jadid movement in Central Asia and its emergence, the role of Mahmudkhoj Behbudi in the Jadid movement and its relevance, how their ideas were continued by their followers, and their significance today.
Keywords: Jadid movement, new method schools, Jadid press, enlightenment, national awakening, social consciousness.